Electrochemical performance of mixed carbon material with waterproof membrane for lithium air battery in the ambient atmosphere. (September 2015) - Yuan, Jiashu; Zhu, Yongming; Gao, Jian; Li, Wantang
Abstract: A waterproof membrane made in-house is applied on the lithium air battery, which can effectively block the water molecules and carbon dioxide in the air, so as to reduce the occurrence of the side reaction, e.g. lithium ions react with water or carbon dioxide to form lithium hydroxide or lithium carbonate. Physicochemical analyses are conducted via XRD (X-ray diffraction), SEM (scanning electron microscope), nitrogen adsorption-desorption, EIS (electrochemical impedance spectroscopy) and LSV (linear sweep voltammetry) test. Under different hydrothermal reaction time and temperatures, α-MnO2 specific surface area, pore size distribution and catalytic properties are evaluated. The first and second discharge capacities are 649.5 mA h/g and 775.4 mA h/g, respectively. The relationship between the air electrode with graphite mixed Super P and α-MnO2 is evaluated as well as the relationship between pore size distribution and the battery discharge performance. An air electrode structure model is also established. Highlights: All electrochemistry characterizations were achieved in the ambient atmosphere. A first made waterproof membrane can reduce the occurrence of the side reaction. A cathodal structure model was constructed.